Comparison of Cardiovascular Risk Estimation Tools in Thai Hospital Employees - Sukontasarn, MD, Apichard; Chaiwong, BSc, MPH, Warut; Thepsen, MD, Khajornsak; Chomsang, MD, Prinya; Samranthin, MD, Manoon; Suwanjutah, MD, Thouantosaporn; Suwannakijboriharn, MD, Chokechai; Manosroi, MD, Worapaka; Saikam, BNS, MSc, Jutarut; Boonma, MPH, Chulathip; Kunanusont, MD,PhD, Chaiyos (The Bangkok Medical Journal, 2021)
OBJECTIVES: To compare cardiovascular disease (CVD) risks estimated by various estimators, we collected and analyzed the annual health checkup data of nonphysician hospital employees (NPHEs) in 5 private hospitals in Thailand in 2018. MATERIALS AND METHODS: This cross-sectional study employed five commonly used CVD risk calculators Thai Cardiovascular (CV) Risk score, modified Coronary Risk Chart (mCRC), Systematic Coronary Risk Evaluation (SCORE) chart, World Health Organization-Southeast Asian Region B (WHO SEAR B) risk prediction chart, and atherosclerotic cardiovascular disease (ASCVD) risk estimator plus) to compare risk levels estimated by each method. Statistical analysis was conducted using R code and STATA. RESULTS: Among 7,286 eligible NPHEs invited to join, 3,687 consented to join. A total of 2,907 subjects were included in this study after excluding those with inadequate data and those with existing CVD. The majority (84.7%) of subjects were female and 75.3% of subjects were in the 30-59 years’ age group. More than half (64.6%) had normal Body Mass Index (BMI). A small proportion had pre-existing hypertension (16.4%), diabetes mellitus (7.9%) and very few reported smoking behavior (5.1%) while a quarter (24.2%) reported regular alcohol use and 60.6% reported sedentary life. Pairwise comparison of future 10-year CVD risks between Thai CV Risk Score and (i) mCRC, (ii) European SCORE, (iii) WHO SEAR B risk chart and, (iv) ASCVD Risk Estimator Plus showed significant agreement of 94.15%, 98.25%, 97.80%, and 98.83% respectively, all with p < 0.001. Comparing results of Thai CV Risk Score when lipid profiles was used and not used also revealed high agreement (88.72%), p < 0.001. Subgroup comparison among those with moderate to high risks, agreement between Thai CV Risk Score with m-CRC, European SCORE, WHO SEAR-B and ASCVD Risk Estimator Plus dropped dramatically to 47.1%, 78.6%, 20.0%, and 41.7% respectively. CONCLUSION: This study shows significant agreement between the Thai CV Risk Score with lipid profiles and mCRC, European SCORE Chart, WHO SEAR B, ASCVD Risk Estimator Plus and Thai CV Risk Score without lipid profiles. The Thai CV Risk Score could numerically detect more persons with moderate or high cardiovascular risk than other risk calculators. Clinical recommendation for those with moderate or even low risk should be made carefully, taking into account that the patient might actually be at a higher risk level.